Self-determination theory: its application to health behavior and complementarity with motivational interviewing - Patrick Heather; Williams Geoffrey C (BMC, 2012)
Abstract Mounting evidence implicates health behaviors (e.g., nutrition, physical activity, tobacco abstinence) in various health outcomes. As the science of behavior change has emerged, increasing emphasis has been placed on the use of theory in developing and testing interventions. Self-determination theory (SDT)-a theoretical perspective-and motivational interviewing (MI)-a set of clinical techniques-have both been used in health behavior intervention contexts. Although developed for somewhat different purposes and in relatively different domains, there is a good deal of conceptual overlap between SDT and MI. Accordingly, SDT may offer the theoretical backing that historically has been missing from MI, and MI may offer SDT some specific direction with respect to particular clinical techniques that have not been fully borne out within the confines of health related applications of SDT. Research is needed to empirically test the overlap and distinctions between SDT and MI and to determine the extent to which these two perspectives can be combined or co-exist as somewhat distinct approaches.